Comparison of Neutrophyl Lymphocyte Ratio and Nerve Conduction Study Between Male Type 2 Diabetes Mellitus With or Without Peripheral Neuropathy Complication - Martha Kurnia Kusumawardani; Surdiana; I Putu Alit Pawana; Sony Wibisono (Indonesian Journal of Physical Medicine & Rehabilitation, 2022)
ABSTRACT Background: Diabetic Peripheral Neuropathy (DPN) is one of the type 2 Diabetes Melitus (T2DM) complication, which may lead to diabetic foot ulcer and lower extremity amputation. Inflammation plays a role in the pathogenesis of this type 2 DM complication. Recent studies showed neutrophyl-lymphocyte ratio (NLR) is a potential inflammation marker. Early screening for neuropathy is an important part of the medical rehabilitation management of this condition. Material and methods: This study uses data analysis independent sample T-2 test with a significant (p<0.05). This study is a analytic observation cross-sectional study with type 2 diabetic male subjects, screened with Michigan Neuropathy Screening Instrument then divided into 2 groups, with DPN group (11 subjects) and without DPN group (7 subjects). This was followed with complete blood count laboratory testing (neutrophyl and lymphocyte level) and NCS to measure distal latency, amplitudo, and NCV of the tibial, peroneal, and suralnerve on both lower extremities. Result: There were 18 subjects in this study. Independent T-2 test showed that there was no significant difference in neutrophils (p=0.679), lymphocytes (p=0.127), and NLR (p=0.190) in the DM group without or with neuropathy. NCS showed that there were significant differences on the amplitude of the three nerves peroneal (p=0.003), tibial (p=0.017), sural (p=0.033), also in NCV of peroneal (p=0.001) and tibial (p=0.008). There were no significant differences found on the three distal latency of peroneal (p=0.074), tibial (p=0.151), sural(p=0.294), and NCV of sural (p=0.262). Conclusions: This study shows that there is no significant difference in NLR on both groups. There were significant differences in the amplitude of the three peroneal, tibial, and sural nerves and the conduction velocity of the peroneal and tibial nerves. However, there was no significant difference in the distal latency of the threeperoneal, tibial, sural, and the NCV of the sural nerves.Keywords: diabetes melitus, diabetic peripheral neuropathy, nerve conduction studies, neutrophyl-lymphocyte ratio, rehabilitation management.